2009
DOI: 10.1089/cbr.2008.0588
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Phase II Study of Vandetanib Plus Docetaxel/Prednisolone in Patients with Hormone-Refractory Prostate Cancer

Abstract: Vandetanib (ZACTIMA) is a once-daily oral anticancer drug that selectively inhibits vascular endothelial growth factor receptor, epidermal growth factor receptor, and rearranged during transfection signaling. This randomized (1:1), double-blind study evaluated vandetanib (100 mg/day) or placebo in combination with docetaxel (D; 75 mg/m(2) every 3 weeks) and prednisolone (P; 2 x 5 mg/day) in 86 patients with metastatic hormone-refractory prostate cancer (mHRPC). The primary assessment was prostate-specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The highest occurrence (30.8%; 95% CI, 26.7-35.0%) was seen in a Phase III trial for ovarian cancer [69], whereas the lowest overall incidence was detected in ten trials that reported no sign of high-grade hypertensive events [27, 33, 36, 46, 56, 62, 63, 75, 78, 85]. A random-effects model (c 2 -based Q-statistic test: q = 1065.86; P < 0.001; I 2 = 93.4%) revealed that the total occurrence of all-grade hypertensive occasions in cancer patients treated with VEGFR-TKIs was 4.4% (3.7-5.0%, 95% CI, Supplementary Table 4 and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The highest occurrence (30.8%; 95% CI, 26.7-35.0%) was seen in a Phase III trial for ovarian cancer [69], whereas the lowest overall incidence was detected in ten trials that reported no sign of high-grade hypertensive events [27, 33, 36, 46, 56, 62, 63, 75, 78, 85]. A random-effects model (c 2 -based Q-statistic test: q = 1065.86; P < 0.001; I 2 = 93.4%) revealed that the total occurrence of all-grade hypertensive occasions in cancer patients treated with VEGFR-TKIs was 4.4% (3.7-5.0%, 95% CI, Supplementary Table 4 and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 outlined the selection process in detail. These trials represented three studies with sorafenib, 21,31,32 three with sunitinib, 20,33,34 three with vandetanib [35][36][37] and five with pazopanib. 2,[38][39][40][41] The characteristics of each included trial were presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Horti et al . [52] conducted a randomized, double-blind, phase II study, investigating vandetanib (100 mg/day) vs. placebo, in combination with docetaxel (75 mg/m² every three weeks) and prednisolone (10 mg/day). This study included 86 patients with metastatic HRPC.…”
Section: Results Of the Main Clinical Studies Of Therapies Targetimentioning
confidence: 99%